2001
DOI: 10.1038/sj.ijo.0801689
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of obesity: practical implications

Abstract: Over the past years substantial progress has been made in the molecular elucidation of monogenic forms of obesity both in rodents and in humans. In addition, several quantitive trait loci have been mapped in mice. In humans, non-parametric linkage studies have led to the identification of relevant chromosomal regions, some of which have already been confirmed. In this review we focus on an interpretation of the heritability estimates obtained in twin, family and adoption studies. These estimates include both d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 66 publications
0
28
0
1
Order By: Relevance
“…38 Parental BMI was not associated with the therapeutic outcome in the current study; however, sib-sib BMI correlations have consistently been higher than parent-offspring correlations. 37 Another explanation, however, might be that the presence of an obese sibling not attending the program and thus sticking to his/her eating and sedentary habits may discourage the index child in his/her efforts to change that behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Parental BMI was not associated with the therapeutic outcome in the current study; however, sib-sib BMI correlations have consistently been higher than parent-offspring correlations. 37 Another explanation, however, might be that the presence of an obese sibling not attending the program and thus sticking to his/her eating and sedentary habits may discourage the index child in his/her efforts to change that behavior.…”
Section: Discussionmentioning
confidence: 99%
“…37 Because an obese sibling predicted a poor outcome, we hypothesize that, in these cases, genetic factors account for an obesity phenotype less amenable to weight reduction programs. Indeed, in a recent study, we were able to show that children with a specific insulininduced gene 2 genotype fared less well in such a program.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and associated metabolic alterations are growing problems in public health [2,7,8]. Although a positive energy balance is likely to be a final common pathway for obesity, changes in eating behaviour and genetic susceptibility are factors that have emerged recently [2,9].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Several mutations of the MC4R, mainly one nonsense (Tyr-35-Stop) and three frameshift mutations (732-733insGATT, 631-634delCTCT, 47-48insG) can be considered loss-of-function mutations and are associated with dominant inheritance of obesity. Functional studies showed that many of the missense muations also lead to a loss of function of the MC4R.…”
Section: Introductionmentioning
confidence: 99%